Energy levels of rare-earth ions in crystal lattice sites of cubic symmetry - Ammerlaan, C.A.J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Numerical calculations are presented for the energy levels of the rare-earth ion Er³⁺ in a crystalline field of cubic symmetry. A distinction is made between the five different point groups within the system of cubic symmetry. Traditionally only the point groups O, Oh and Td are considered. As an extension, in the present analysis the effect of an additional crystal-field term appearing for the cubic point groups T and Th is explored.